2013
DOI: 10.1016/j.ijdevneu.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia alters milk neurotrophins and long chain polyunsaturated fatty acids

Abstract: The present study suggests that there is a differential regulation of DHA and neurotrophins in breast milk in preeclampsia and are associated with growth parameters of children. Future studies should explore the associations between milk LCPUFA, neurotrophins with neurodevelopment in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Furthermore, in another study carried by Danget et al, 32 they reported that levels of breastmilk BDNF are highest at Day 3 after birth, then decrease at 1.5 months of age, and then increase until 6 months; they explained these significant differences in BDNF levels at several time points during lactation as due to the adaptive changes of the preeclamptic mothers, and they suggested that neurotrophin is altered in preeclampsia. By using the Bayley Scale of Infant Development, Second Edition (BSID-II) cognitive assessment, Nassar et al 33 found that breastfed infants had higher Bayley Scale scores, followed by mixed-fed and then formula-fed infants, and the serum BDNF levels were significantly higher in breastfed infants compared with infants who received formula milk.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in another study carried by Danget et al, 32 they reported that levels of breastmilk BDNF are highest at Day 3 after birth, then decrease at 1.5 months of age, and then increase until 6 months; they explained these significant differences in BDNF levels at several time points during lactation as due to the adaptive changes of the preeclamptic mothers, and they suggested that neurotrophin is altered in preeclampsia. By using the Bayley Scale of Infant Development, Second Edition (BSID-II) cognitive assessment, Nassar et al 33 found that breastfed infants had higher Bayley Scale scores, followed by mixed-fed and then formula-fed infants, and the serum BDNF levels were significantly higher in breastfed infants compared with infants who received formula milk.…”
Section: Discussionmentioning
confidence: 95%
“…While breast milk DHA was not reported in either of these studies, it is important to note that these studies were conducted in Egypt and China, where DHA intake may have differed from our study population. Dangat et al used a different ELISA kit not specifically identified for use with human milk and reported breast milk BDNF concentrations in the range of 300 pg/mL, with significant differences between women with preeclampsia and healthy controls [24,56]. Breast milk DHA concentrations were also reported and were significantly higher in women with preeclampsia, though mean concentrations in both groups were well below the worldwide average of 0.30% [56].…”
Section: Brain Derived Neurotrophic Factormentioning
confidence: 99%
“…Dangat et al used a different ELISA kit not specifically identified for use with human milk and reported breast milk BDNF concentrations in the range of 300 pg/mL, with significant differences between women with preeclampsia and healthy controls [24,56]. Breast milk DHA concentrations were also reported and were significantly higher in women with preeclampsia, though mean concentrations in both groups were well below the worldwide average of 0.30% [56]. Both Li and Ismail reported centrifuging samples at speeds higher than those provided in the manufacturer's instruction while Dangat did not describe sample preparation protocols.…”
Section: Brain Derived Neurotrophic Factormentioning
confidence: 99%
“…The first study shows that DHA and nervonic acid concentrations were higher in the colostrum of the PE group, as compared to the normotensive control group. The second study shows that DHA concentrations were also higher at day 3, and at 1.5 and 3.5 months ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fares et al ( 22 ) evaluated the total fatty acid profile of colostrum in mothers who delivered preterm and found lower DHA levels and higher Arachidonic Acid (AA) levels, AA:DHA, and ω6:ω3 ratios in the PE group. Dangat et al ( 23 , 24 ) published two studies focused on long chain polyunsaturated fatty acids. The first study shows that DHA and nervonic acid concentrations were higher in the colostrum of the PE group, as compared to the normotensive control group.…”
Section: Introductionmentioning
confidence: 99%